Morning Exercise Reduces Abdominal Fat and Blood Pressure in Women; Evening Exercise Increases Muscular Performance in Women and Lowers Blood Pressure in Men - Arciero, Paul J.; Ives, Stephen J.; Mohr, Alex E.; Robinson, Nathaniel; Escudero, Daniela; Robinson, Jake; Rose, Kayla; Minicucci, Olivia; O’Brien, Gabriel; Curran, Kathryn; Miller, Vincent J.; He, Feng; et al. (Frontiers in Physiology, 2022)
The ideal exercise time of day (ETOD) remains elusive regarding simultaneous effects on health and performance outcomes, especially in women. PURPOSE: Quantify health and performance outcomes in women and men adhering to different ETOD. METHODS: Thirty exercise-trained women (BMI = 24±3 kg/m2; 42±8 yrs) and twenty-six men (BMI = 25.5±3 kg/m2; 45±8 yrs) were randomized to multimodal ETOD in the morning (0600-0800h, AM) or evening (1830-2030h, PM) for 12 weeks and analyzed as separate cohorts. Baseline (week 0) and post (week 12) muscular strength (1-RM bench/leg press), endurance (sit-ups/push-ups) and power (squat jumps, SJ; bench throws, BT), body composition (iDXA; fat mass, FM; abdominal fat, Abfat), systolic/diastolic blood pressure (BP), respiratory exchange ratio (RER), profile of mood states (POMS), and dietary intake were assessed. RESULTS: Twenty-seven women and twenty men completed the 12-week intervention. No differences at baseline existed between groups (AM vs. PM) for both women and men. In women, significant interactions (p<0.05) existed for 1RM bench (8±2 vs. 12±2, ∆kg), pushups (9±1 vs. 13±2, ∆reps), BT (10±6 vs. 45±28, ∆watts), SJ (135±6 vs. 39±8, ∆watts), fat mass (-1.0±0.2 vs. -0.3±0.2, ∆kg), Abfat (-2.6±0.3 vs. -0.9±0.5, ∆kg), diastolic (-10±1 vs. -5±5, ∆mmHg) and systolic (-12.5±2.7 vs. 2.3±3, mmHg) BP, AM vs. PM, respectively. In men, significant interactions (p<0.05) existed for systolic BP (-3.5±2.6 vs. -14.9±5.1, ∆mmHg), RER (-0.01±0.01 vs. -0.06±0.01, ∆VCO2/VO2), and fatigue (-0.8±2 vs. -5.9±2, ∆mm), AM vs. PM, respectively. Macronutrient intake was similar among AM and PM groups. CONCLUSION: Morning exercise (AM) reduced abdominal fat and blood pressure and evening exercise (PM) enhanced muscular performance in women, whereas, PM increased fat oxidation and reduced systolic BP and fatigue in men. Thus, ETOD is important to optimize individual exercise-induced health and performance outcomes and may be independent of macronutrient intake. This study was registered with ClinicalTrials.gov Identifier: NCT02593656.